2019
DOI: 10.1136/tsaco-2019-000351
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients with gunshot wounds to the brain

Abstract: IntroductionGunshot wounds to the brain (GSWB) confer high lethality and uncertain recovery. It is unclear which patients benefit from aggressive resuscitation, and furthermore whether patients with GSWB undergoing cardiopulmonary resuscitation (CPR) have potential for survival or organ donation. Therefore, we sought to determine the rates of survival and organ donation, as well as identify factors associated with both outcomes in patients with GSWB undergoing CPR.MethodsWe performed a retrospective, multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Aggressive resuscitation improves patients’ eligibility for organ donation and, in some cases, their chance of survival 32 40 41. A multicenter study demonstrated that even in patients with cranial gunshot wounds undergoing cardiopulmonary resuscitation (CPR), 2.1% survived to discharge, and 17.5% of non-survivors were eligible donors 42…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggressive resuscitation improves patients’ eligibility for organ donation and, in some cases, their chance of survival 32 40 41. A multicenter study demonstrated that even in patients with cranial gunshot wounds undergoing cardiopulmonary resuscitation (CPR), 2.1% survived to discharge, and 17.5% of non-survivors were eligible donors 42…”
Section: Discussionmentioning
confidence: 99%
“… 32 40 41 A multicenter study demonstrated that even in patients with cranial gunshot wounds undergoing cardiopulmonary resuscitation (CPR), 2.1% survived to discharge, and 17.5% of non-survivors were eligible donors. 42 …”
Section: Discussionmentioning
confidence: 99%
“…35 Organ donation has been identified as a valid secondary outcome in patients with fatal PBI, with organ donation rates as high as 71% after implementation of aggressive donor care protocols, including hormone replacement therapy. 7,36 Lack of appropriate resuscitative efforts or early termination in patients suffering from PBI may lead to lower organ procurement rates. The presence of a multidisciplinary team and in-house coordinators from OPOs may lead to substantial improvements in donation rates.…”
Section: The Transplantation Perspectivementioning
confidence: 99%
“…This may be due to confounding factors such as sympathomimetic/parasympatholytic drugs, bullets causing direct oculomotor nerve pressure from a localized hematoma, and optic nerve or direct ocular trauma, which deviates from uncal herniation seen with a space-occupying lesion in blunt traumatic brain injury. [6][7][8] There is also the question of whether patients with either isolated or multicavitary PBI should undergo cardiopulmonary resuscitation or even EDT. A recent multicenter study of patients with PBI receiving cardiopulmonary resuscitation alone demonstrated a dismal 2.1% survival rate (with 74% of these discharged to rehabilitation or home), but a 10.3% organ donation rate.…”
Section: Introduction-the Trauma Surgery Perspectivementioning
confidence: 99%
See 1 more Smart Citation